Creative writing (Poetry): An Exercise in Pedagogy - Singh, Pushpraj; Jayoti , Ekta Rana; Gautam , Kripa Krishna (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present research is to sensitize the tertiary level learners to the varied semantic connotations of lexical items through exercises in creative writing. To achieve the intended objective a four- tier pedagogy has been developed: Building lexical repertoire, motivating the learners for Creative use of the given lexical items with discreet Teacher Prompts and Finese through collaborative efforts of the learners. The hypothesis has been corroborated by the experiments carried out on three categories of students: Undergraduates, Post-Graduates and Research Scholars.